Modern Tendencies in Improving the Content and Steps of Involving Students in Scientific Activity in the Field of Physical Culture - Madaminov Аzimbek Egamberganovich (International Journal on Integrated Education, 2022)
This article focuses on improving the prospects of this field of education in the future through the positive implementation of scientific and creative activities of specialists who can meet the parameters of the implementation of scientific and creative work of students in the field of physical culture.